Stillness is the key - Ryan Holiday (London Profile Books, 2019)
Throughout history, there has been one quality that great leaders, makers, artists and fighters have shared. The Zen Buddhists described it as inner peace, the Stoics called it ataraxia and Ryan Holiday calls it stillness: the ability to be steady, focused and calm in a constantly busy world.drawing on a wide range of history's greatest thinkers, Holiday shows us how crucial stillness is, and how it can be cultivated in our own lives today. Just as Winston Churchill, Oprah Winfrey and baseball player Sadaharu Oh have done, we can all benefit from stillness to feed into our greater ambitions - whether building a business or simply finding happiness, peace and self-direction.Stillness is the key to the self-mastery, discipline and focus necessary to succeed in this competitive, noisy world.
Keywords: Psychology